Determination of Meat and Fish Identities in Raw and Processed Food Samples Using PCR-RFLP Technique - Murugaiah, Chandrika (2006)
The opening up of international food markets has resulted in the establishment of new regulations to ensure fair practices in the food trade. The identification of animal species is one of the areas of major concern for food hygiene laboratories, in forensic medicine and in the quality control of animal products. Food quality and safety will be strongly improved by the EC legislation (178/2002) on food traceability, which came into force in January 2005. The restriction fragment length polymorphism (RFLP) methodology has advanced genotyping of animal species, although further improvements are definitely needed. This study describes an investigation into the use of a PCR-RFLP technique as a routine analytical tool for species testing since accurate analytical methods are needed to ensure compliance with the new regulations. PCR-RFLP procedure was improved for the genotyping of beef, pork, buffalo meat, beef frankfurter (three brands), minced beef (two brands), pork frankfurter (two brands) and pork cocktail (one brand). Eight types of meat, 19 types of fish and 16 types of processed food samples were included as control samples. A highly conserved segment within the cyt b gene was selected for PCR amplification by the universal primers cyt b1 and cyt b2 with the hope that it would amplify the cyt b gene from all the tested species. Apart from tuna fish and meats from quail, chicken, goat, beef, pork, buffalo, deer and rabbit samples, most of the fish samples were not identified using the cyt b primers. Genotyping of species by the present RFLP method was accomplished with amplifying a 359 bp region within the cyt b gene and digesting the amplified product using AluI, HindIII, BsaJI, RsaI, BstNI, MseI, NsiI and BstUI enzymes. The specificity of the method was successfully assessed by RFLP analysis of meats from quail, chicken, goat, beef, pork, buffalo, deer, rabbit and tuna fish. PCR-RFLP technique showed high discriminatory power, but not all the species tested were identified. The concerted implementation of these conditional protocols for species identification was evaluated with beef frankfurter, minced beef, pork frankfurter and pork cocktail samples, and was found to be discriminatory for species identification. Commercial frauds through species substitution were not detected and the expected meat was present from the processed food samples tested. This PCR-RFLP based assay demonstrated to be an easy technique in routine analysis of raw and processed food for the detection of meat species.